Bidirectional relationship between physical health symptoms and depressive symptoms in the pre- and postpartum period. - Gómez-Pérez, Lidia; Cumsille, Patricio; Román, Camila (Elsevier, 2020)
Objective: To test the bidirectional relationships between physical health symptoms (PHS) and depressive symptoms (DS) as well as between the intensity of 'any pain' and DS in the pre- and postpartum period METHOD: Women (N = 615) completed the Edinburgh Postnatal Depression Scale, the Patients Health Questionnaire-15, and numerical pain rating scales when they were between 32 and 37 weeks of gestation, and subsequently one, three, and six months postpartum. We conducted two random intercept cross-lagged panel models (RI-CLPM) RESULTS: Both models presented excellent fits. The relationship between PHS and DS was bidirectional across all the data waves (χ2(9) = 6.610, p = .678, CFI = 1, TLI = 1, RMSEA = 0). The magnitude of the standardized cross-lagged regression coefficient was relatively similar from DS to PHS (raging between 0.081 and 0.171); and from PHS to DS (raging between 0.121 and 0.138). The relationship between 'any pain' intensity and DS was also bidirectional, but only during the postnatal period (χ2(9) =11.765, p = .227, CFI = 0.99, TLI = 0.98, RMSEA = 0.022). The magnitude of the standardized cross-lagged regression coefficient was higher from DS to 'any pain' intensity (raging between 0.214 and 0.216); than from 'any pain' intensity to DS (raging between 0.092 and 0.097). Conclusions: Concurrently intervening over physical and mental health symptoms could promote women's perinatal health.
https://openpolicyfinder.jisc.ac.uk/id/publication/14084
Keywords: Depresión postparto; Enfermedades mentales en el embarazo; Mujeres embarazadas - Salud e higiene; Depression; Pain; Physical health; Postpartum; Prospective longitudinal study; RI-CLPM